Soil Formation and Taxonomy in Yeşilırmak River Terraces - Alper Durak; Mehmet Erdem Aydın (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the soils of which parent material is alluvial and formed Yeşilırmak river terraces were investigated. For this purposes four different profiles were excavated in the study area. Then twenty-seven soil samples were taken from horizons of four profiles and their physical and chemical analyses were done for soil taxonomy research. Profile of Kumocagi and Cakil were classified in subgroup as Typic Ustipsamments, Havaalanı and Mera profiles were classified Typic Haplustolls and Typic Argiustolls subgroups respectively. The pH values of soils varied between 7.38-8.41. These soils can be classified as low and highly basic. Most of the soil series had an irregular pH distribution in the profile. The range of carbonate content of the soils was 0.8-25.4%. Although carbonate content of soils showed a very wide range, majority of them can be classified as highly calcareous. In most of soils carbonate content was distributed irregulary in the profile. Organic matter content were between 0.14-6.11% in the soils. Although organic matter contents of the soils changed in a wide range most of them had low organic matter content. Organic matter content was over 4% in the surface horizon of only two profiles. Research result showed that, alluvial parent material, particle size, topograpy and time have different effect on investigation soils.